2005
DOI: 10.1111/j.1463-1318.2005.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

The SCAR‐3 study: 5‐year adhesion‐related readmission risk following lower abdominal surgical procedures

Abstract: Objective The Surgical and Clinical Adhesions Research (SCAR) and SCAR-2 studies demonstrated that the burden of adhesions following lower abdominal surgery is considerable and appears to remain unchanged despite advances in strategies to prevent adhesions. In this study, we assessed the adhesion-related readmission risk directly associated with common lower abdominal surgical procedures, taking into account the effect of previous surgery, demography and concomitant disease.Methods Data from the Scottish Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
155
1
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(175 citation statements)
references
References 14 publications
7
155
1
12
Order By: Relevance
“…Adhesions develop after abdominal surgery as a result of peritoneal trauma and subsequent inflammation2. Among patients undergoing abdominal surgery, those with a rectal resection have the highest adhesion‐related readmission rates1 3, 4, and adhesiolysis‐related procedures are associated with high inpatient expenditure5.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesions develop after abdominal surgery as a result of peritoneal trauma and subsequent inflammation2. Among patients undergoing abdominal surgery, those with a rectal resection have the highest adhesion‐related readmission rates1 3, 4, and adhesiolysis‐related procedures are associated with high inpatient expenditure5.…”
Section: Introductionmentioning
confidence: 99%
“…The Surgical and Clinical Adhesion Research (SCAR) study reported that open colorectal, surgical procedures resulted in the highest risk of adhesion-related readmissions of all types of abdominal surgery [5,6]. Laparoscopic techniques are associated with less surgical trauma, and one hypothesis concerning laparoscopy as a surgical technique has been that the risk for adhesion formation postoperatively would be lower than after open surgery.…”
mentioning
confidence: 99%
“…The SCAR-3 study demonstrated that Crohn's disease had no effect on risk while colorectal cancer decreased ones risk of readmission. Higher risk was noted in those patients younger than 60 years of age and a history of peritonitis [14]. However, the age of the patient is not so straightforward.…”
Section: Discussionmentioning
confidence: 96%
“…The incidences of readmissions and small bowel obstructions following laparotomy have been extensively studied in the Surgical and Clinical Adhesions Research (SCAR) studies. There is a 5% -9% risk of readmission directly related to adhesions after lower abdominal surgery [14], [15] but this risk is nearly 20% after proctocolecomy with ileal-pouch anastomosis [16]. It has also been shown that the rates of adhesion related readmissions increase every year after open colorectal surgery.…”
Section: Discussionmentioning
confidence: 97%